Investigation of precision task demands on workers' muscular activities, heart rate, and perceived exertion rating. - Ramadan, Mohamed Z.; Alferdaws, Fares F. (Work, 2022)
BACKGROUND: Manual material handling (MMH) tasks significantly contribute to musculoskeletal disorders in manual workers. OBJECTIVES: In this study, we assessed the physical factors of precision lifting tasks that affect muscular activities (electromyography, EMGs), heart rate, and perceived exertion rating in ten healthy male workers aged 25–35 years, while considering the safety aspect of the common types of safety footwear. METHODS: The independent variables that were assessed are as follows: 1) lifting method (precise and inexact), 2) lifting frequency (one and four liftings/min), and 3) type of safety footwear worn by the worker (light, medium, or heavy). The response variables data, represented by EMG signals, for four muscular activities (biceps brachii, deltoid, trapezius, and erector spinae), heart rate, and perceived exertion were analyzed using a three-factor within-subjects design. RESULTS: The results showed that wearing heavy safety shoes increases the effort used with precise lifting methods in trapezius and erector spinae muscular activities. We also observed that the heart rate and perceived exertion increased rapidly at four lifts/min compared to one lift/min, regardless of the lifting method. CONCLUSIONS: The advantages of choosing appropriate safety footwear must be carefully assessed before replacing the conventional working safety shoes.